2019
DOI: 10.3727/152599518x15403853721231
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Grassroots Participant Legacy of Major Sporting "Supplemental" Events

Abstract: For a considerable time, major sporting events have been investigated to explore their "participation" legacy impact (effect on participation in sports at the grassroots level), often with mixed results. In this article, the authors propose an approach to examine not major events themselves, but adjacent, supplemental events, and whether such events can contribute to a participation legacy. The authors do this by developing a "grassroots participation ladder," built on the transtheoretical model, which has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The study involved 152 short interviews (Trophy Tour 100; Fan Zone 52) with visitors to these supplemental events. Full details of the study can be found in Burgess, Bingley & Urwin (2019). The interviews examined attendees' thoughts and observations about the supplemental events and were conducted from late December 2014 until the end of CWC2015 in March 2015.…”
Section: Methodsmentioning
confidence: 99%
“…The study involved 152 short interviews (Trophy Tour 100; Fan Zone 52) with visitors to these supplemental events. Full details of the study can be found in Burgess, Bingley & Urwin (2019). The interviews examined attendees' thoughts and observations about the supplemental events and were conducted from late December 2014 until the end of CWC2015 in March 2015.…”
Section: Methodsmentioning
confidence: 99%